Gender differences in core muscle morphology of elite alpine skiers: insights from ultrasonography - Romero-Morales, C.; Villafañe, J. H.; Jácome-López, R.; Tullio, M.; Strelczuk, A.; Miñambres-Martín, D.; Lara-Cabrero, J. L.; Jiménez-Sáiz, S. L. (Sensors, 2024)
This study investigates gender differences in core muscle morphology among elite alpine skiers using ultrasonography, highlighting significant disparities that could influence training and injury prevention strategies. Methods: A cross-sectional design was employed, examining ultrasound imaging (USI) in 22 elite skiers (11 male, 11 female) to assess the thickness of the external oblique (EO), internal oblique (IO), transversus abdominis (TrAb), and rectus abdominis (RA) muscles. Results: Significant differences were noted, with male skiers displaying greater muscle thickness, particularly in the right IO and RA and left IO, EO, TrAb, and RA. Conclusions: These findings suggest that male and female skiers may require different training approaches to optimize performance and reduce injury risks. This research contributes to a deeper understanding of the physical demands on elite skiers and underscores the need for gender-specific training regimens to enhance athletic outcomes and prevent injuries.